Engram-specific transcriptome profiling of contextual memory consolidation - Rao-Ruiz, Priyanka (Nat Commun, 2019)
Sparse populations of neurons in the dentate gyrus (DG) of the hippocampus are causally implicated in the encoding of contextual fear memories. However, engram-specific molecular mechanisms underlying memory consolidation remain largely unknown. Here we perform unbiased RNA sequencing of DG engram neurons 24 h after contextual fear conditioning to identify transcriptome changes specific to memory consolidation. DG engram neurons exhibit a highly distinct pattern of gene expression, in which CREB-dependent transcription features prominently (P = 6.2 × 10(−13)), including Atf3 (P = 2.4 × 10(−41)), Penk (P = 1.3 × 10(−15)), and Kcnq3 (P = 3.1 × 10(−12)). Moreover, we validate the functional relevance of the RNAseq findings by establishing the causal requirement of intact CREB function specifically within the DG engram during memory consolidation, and identify a novel group of CREB target genes involved in the encoding of long-term memory.